STANLEY CENTER GLOBAL COMPETENCE RESEARCH - Овчаренко, Олена (SWorldJournal, 2025)
In the article, the author analyzes global competence in research conducted by the Stanley Center (USA). From 1994 to 1996, the Stanley Center and the American Council for International Intercultural Education (ACIIE) held two important conferences, the f